Analysis of Material Inventory Control Management for Structural Works using Economic Order Quantity, Reorder Point, and Safety Stock Methods in a 2.5-Storey Boarding House Construction Project - Wyldan Candra Kurniawan; Masca Indra Triana (International Journal Science and Technology, 2025)
This study presents a comprehensive computational analysis of material inventory control management for structural works in a 2.5-storey boarding house construction project located in Jelambar, West Jakarta. The research utilizes the integrated Economic Order Quantity (EOQ), Safety Stock (SS), and Reorder Point (ROP) methods to determine optimal order quantities, safety buffers, and ordering trigger points for key structural materials. The study adopts a quantitative descriptive approach with a case study method. Data was collected through interviews, site observation, and analysis of secondary documents, including the Bill of Quantities (BoQ) and the time schedule (S-curve). The analysis focused on seven major materials, including cement, reinforcing steel (D13 and Ø8), and Class III timber. The calculated EOQ values, which minimize the sum of ordering and holding costs, showed that the project should order, for example, 271 sacks of cement, 85 bars of D13 steel, and 586 pieces of Class III timber. Corresponding Safety Stock levels were calculated using a 95% service level , resulting in a required buffer of 95 sacks of cement and 113 bars of D13 steel. The Reorder Point (ROP) values indicate when a new order should be placed, such as 313 sacks of cement and 400 bars of D13 steel. A cost comparison demonstrated that the project's initial total inventory cost was IDR 20,005,302. Applying the EOQ-only policy resulted in a cost efficiency of 34.88%. Crucially, the combined implementation of the EOQ, Safety Stock, and Reorder Point policy led to a significant reduction in total inventory costs to IDR 9,750,733, achieving a cost efficiency of 51.26% compared to the initial condition. This confirms that the integrated quantitative approach is highly effective for optimizing material ordering, mitigating stock-out risk, and substantially reducing inventory costs in small-to-medium scale urban construction projects with site constraints.